Sustenability and Organic Growth Marketing: an Exploratory Approach on Valorisation of Durable Development Principles in Tourism - Gheorghe Epuran; Lavinia Dovleac; Ioana Simona Ivasciuc; Bianca Tescașiu (Amfiteatru Economic Journal, 2015)
Sustainability implies the extension of companies' classic relations outside the economic sphere, leading to the necessity of justification and legitimisation of the actions performed by them and being a premise for organic growth, a concept known as smart growth. This means creating more products – values, for more customers, with superior productivity and proper management of the risks caused by growth itself. In this context, the expression "grow or disappear" is replaced by "improve in order to stay competitive". The objective of this paper is to highlight the way in which the implementation of the sustainable development principles are correlated with the aspects of organic growth in tourism and the possibility of evaluating the organic growth from the perspective of sustainable development. In order to achieve the proposed objective, it was conducted a qualitative marketing research among hotel managers in Bra?ov County. Collected using the quota method, the sample is a non-probabilistic type, and the research was conducted based on semi-structured interview, a method chosen in accordance to the type of research. The major contributions of the research process are to highlight the relation between the sustainable development and organic growth, to propose a general configuration of the marketing strategy pillars of sustainable business in tourism and to identify some methods of evaluating the organic growth from the perspective of sustainable development.
Keywords: L83; M10; M31; Q56; 330; sustainability; marketing; organic/smart growth; sustainable tourism; sustainable development; marketing 3.0